BANKER TO THE POOR AND ITS URGENCY BASED ON INDONESIAN CONTEXT (PERCEIVING THE TOUGHTS AND EXPERIENCES OF MUHAMMAD YUNUS) - Arifa, Laily Nur (Risâlah, Jurnal Pendidikan dan Studi Islam, 2021)
Poverty is not welcome in all types of society. There are many efforts made to overcome this issue. Nevertheless, Muhammad Yunus has made inspirational efforts. His efforts to overcome poverty issues in Bangladesh have escorted him to receive the Nobel award. His model in overcoming the issue by establishing Grameen Bank for the poor has become a role model worldwide, including Indonesia. According to Islamic regulation, bank interest applied by the Grameen Bank is not against Islamic regulation (riba) since the interest will be distributed to its customers. Poverty has become a significant issue for Indonesia and other poor and developing countries worldwide. Therefore, the adaptation of the Grameen Bank model to overcome poverty issues in Indonesia is in urgent demand. There are three may key to adopt the Grameen Bank concept according to the Indonesian context. The first key is to give priority to women for economic development. This policy is that women are less selfish and have more concern towards their children and family. The second key is to establish a group of creditors. This group is expected to encourage each other to repay the loan and support each other under hardship. The third key is to provide unsecured debt. This type of loan is the answer to help the poor to improve their condition. Adequate capital provision will enable the poor to improve their creativity; they can develop their business and improve life quality.